OFFSET EVALUATION OF THE ECUADORIAN VERTICAL DATUM RELATED TO THE IHRS - Sánchez, José L. Carrión; Freitas, Sílvio R. C. de; Barzaghi, Riccardo (Boletim de Ciências Geodésicas, 2018)
Considering the definition of the International Height Reference System (IHRS) in the geopotential space (Resolution 1/2015, International Association of Geodesy - IAG), among the present main objectives of the international geodetic community is the materialization of IHRS around the world. One fundamental task for this is the offset determination of each national vertical datum related to the IHRS. In this manuscript we establish the relationship between the Ecuadorian Vertical Datum (EVD) and the IHRS in the geopotential space following the foundations of the Resolution 1/2015 IAG. Gravity data, heights from the Ecuadorian Fundamental Vertical Network, Global Geopotential Models and Digital Elevation Models were used in the computations. Based on the Least Squares Collocation method, empirical covariance functions and spectral decomposition techniques, we realized the modelling of the geopotential in the study region (4° x 4° centered in the La Libertad tide gauge, Ecuador). Based on the referred approaches, we solved the free Geodetic Boundary Value Problem for determining the discrepancy of the EVD related to the IHRS. An offset of approximately 29 cm ± 3 cm was estimated for the W0 - W0i relation when the GO_CONS_GCF_2_DIR_R5 model was used in the modeling of the medium and long wavelengths of the terrestrial gravity field, and approximately 43 cm ± 3 cm when the EIGEN6C4 model was used.